Lysosome-targeted near-infrared fluorescent dye and its application in designing of probe for sensitive detection of cysteine in living cells. (June 2021) - Liu, Qiuchen; Liu, Chang; Jiao, Xiaojie; Cai, Songtao; He, Song; Zhao, Liancheng; Zeng, Xianshun; Wang, Tianhui
Abstract: The development of methods for real-time monitoring the level of Cys in biological system is a topic of continued importance. Furthermore, the probes emitting in the NIR region are favorable for cell imaging because of their low phototoxcity and high signal-to-noise ratio (S/N) in living cells. In the paper, we have developed a novel lysosome-targeting NIR xanthene-benzothiozolium dye BHCy-OH by taking advantage of the heteroatom replacement strategy to regulate the absorption and emission wavelengths of the known semi-heptamethine dye. Subsequently, the NIR probe BHCy-A with high sensitivity for Cys has been synthesized. The dye BHCy-OH and the Cys-selective probe BHCy-A emitted fluorescence at 735 nm in PBS buffer, and are lysosome-targetable in living cells. Because the lysosome-targeting abilities of them do not demand proton participation, we believe that they are very useful for investigation the function of lysosomes and for interpreting the function of lysosomal Cys in living-cell imaging. Graphical abstract: Novel NIR fluorescence dye BHcy-OH and Cys-sensitive fluorescence probe BHcy-A with lysosome-targeting ability without proton participation have been prepared. Image 1 Highlights: A near-infrared fluorescent probe BHcy-A has been synthesized. The dye BHCy-OH and the Cys-selective probe BHCy-A emitted fluorescence at 735 nm in PBS buffer, and they are lysosome-targetable in living cells. The probe can be used to distinguish efficiently Cys from Hcy and GSH. The probe has been successfully applied to image of lysosomal Cys in living cells.